PENGARUH DAYA TARIK WISATA TERHADAP PROSES PENGAMBILAN KEPUTUSAN KE DESA WISATA KE’TE KESU TANA TORAJA UTARA DI TENGAH PANDEMIK COVID 19 - Seruni Dinitri; Yogi Diarestha (Bogor Hospitality Journal, 2022)
Before the covid 19 pandemic hit the world, tourist visits to North Tana Toraja Regency actually experienced an increase in the number of tourist visits from year to year. But during covid 19 era, when tourists decide to visit a tourist destination, attraction is the most interesting factors in increasing the rate of visits. But during covid 19, visit rate to Ke’te Kesu is sharply decreased. Based on data obtained from the Tourism and Culture Office of North Toraja Regency (2020), it can be seen that the number of foreign tourists in 2020 decreased by 78%, from 32,272 (2019) to 730 (2020). Meanwhile, domestic tourists themselves experienced a decrease of 66%, from 333,166 (2019) to 109,269 tourists (2020). The aim of the researcher is to explore the extent to which the influence of tourist attractions in Ke'te Kesu affects the decision of tourists to visit Ke'te Kesu Touristm Village in the midst of the Covid 19 pandemic. The type of research used in this research is research using a quantitative approach by using Simple Linear Regression. The population in this study are tourists who have visited Ke'te Kesu Tana Toraja Village with a total population of 109,269. The research sample was then calculated using the Slovin formula with a margin of error of 10% with 100 samples. From the results based on the description per dimension, it can be seen that the largest mean is found in the dimension of uniqueness, seasonity and sensitivity. These results indicate that the average respondent comes to Ke'te Kesu Tourism Village because they are interested in the uniqueness of attractions. The seasonality dimension is also large because there is a traditional Rambu Solo ceremony that can be enjoyed at certain times. For sensitivity. For data analysis, there is a very strong relationship between the attraction variable and the decision-making process in Ke'te Kesu Village, Tana Toraja Utara. Tourists will visit because of a very unique attraction that is not found in other areasThis shows that the role of tourist attractions in the tourist village of Ke'te Kesu is so big in attracting tourists during the COVID-19 pandemic.